Improvement of coffee powder weight on nitrogen packing process using lean and six sigma approaches - Nik Alimi Bin Nik Aziz (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose of this project is to blend together the Six Sigma and Lean manufacturing approach to eliminate the inconsistent weight of coffee pack in the nitrogen packing process of food based industries to achieve the stable weight of coffee pack and the Sigma level targeted by organization studied. The focus of this project is on the nitrogen packing process because the inconsistent weight of coffee pack is occurred at this process in packaging department.